Beyond multi-channel marketing : critical issues in dual marketing - Palazzo, Maria; Foroudi, Pantea; Siano, Alfonso (Emerald Publishing Limited, 2020)
'an insightful, conceptual take on the important topic of Dual Marketing. I strongly recommend Beyond Multi-Channel Marketing to all who want to know more about dual, multi- and omni- channel marketing in the digital age.' Charles Dennis, Professor of Consumer Behaviour, Departmental Research Leader, Middlesex University London, UK. The authors of this book delve into the rapidly developing field of dual marketing, investigating the strategic alliances, multi-stakeholder perspectives and branding potential it holds. They promote the adoption of the multichannel approach which is fundamental to facing the challenges of marketing 4.0. Readers will glean innovative and practical insights, providing them with the ability to comprehend the existing link between dual marketing and multichannel marketing and explore its relation to branding and integrated marketing communication. This book also rejuvenates the analysis of the digital context and offers critical advice to organisations interested in online marketing processes. With worldwide appeal, the theoretical and empirical analysis carried out in this book offers cutting edge ideas and techniques to marketing practitioners, supply chain managers and B2B2C company managers looking to understand the digital transformation permeating the whole of organisational life beyond just marketing and communication facets. The book will also be invaluable for doctoral, graduate and postgraduate students in marketing and management.- Resumé vydavatel
Includes index.
Keywords: internetový marketing; marketingový výzkum; marketingový management; Internet marketing; marketing research; marketing management; elektronické knihy; sborníky; electronic books; papers of several authors